Fermentasi Kopi Arabika Menggunakan Fermentor Skala UMKM - Tri Hariyadi; Zahra Nur Salsabila; Gianistri Maulani; Keryanti Keryanti (Fluida, 2022)
Coffee farmer in Babakan Kertasari Village requires a fermenter that can ferment 100 kg of coffee cherries per day to fulfill the market demand. Therefore, the object of this study is to make a coffee fermenter with SMEs scale and to evaluate the performance of the fermenter with the addition of 130 ml/L of Local Microorganism (MOL) made from fermented cassava (cassava tape). Fermentation was carried out for 72 hours in room temperature and in semi-aerobic condition with 14 kg of coffee cherries in SMEs scale fermenter. Evaluation of the fermenter performance was done by analysing pH and ethanol content and organoleptic test of taste and aroma of fermented coffee. The result of analysis shows that fermented Arabica coffee which called cultured coffee fulfilled the National Indonesian Standard (SNI) with pH greater than 4 and caffeine content of 1.97%. Organoleptic test showed that 56% of panellists really like the aroma and 24% of panellists really like the taste of cultured coffee.